The importance of the learning process in ST analysis interpretation and its impact in improving clinical and neonatal outcomes - Susanna Timonen; Kaisa Holmberg (MOSBY-ELSEVIER, 2025)
BACKGROUND: Intrapartum fetal heart rate monitoring was introduced with the goal to reduce fetal hypoxia and deaths. However, continuous fetal heart rate monitoring has been shown to have a high sensitivity but also a high false-positive rate. To improve specificity, adjunctive technologies have been developed to identify fetuses at risk for intrapartum asphyxia. Intensive research on the value of ST-segment analysis of the fetal electrocardiogram as an adjunct to standard electronic fetal monitoring in lowering the rates of fetal metabolic acidosis and operative deliveries has been ongoing. The conflicting results in randomized and observational studies may partly be due to differences in study design.
OBJECTIVE: This study aims to determine the significance of the learning process for the introduction of ST analysis into clinical practice and its impact on initial and subsequent obstetric outcomes.
STUDY DESIGN: This was a prospective observational study with the primary objective to evaluate the importance of the learning period on the rates of metabolic acidosis and operative deliveries after the implementation of ST analysis. The study was conducted at the Turku University Hospital, Turku, Finland, with 3400-4200 annual deliveries. The whole study population consisted of all 42,146 deliveries during the study period 2001 through 2011. The ST analysis usage rate was 18%. The data were collected prospectively from labors monitored with ST analysis as an adjunct to conventional intrapartum fetal heart rate monitoring. Primary endpoints were the rates of metabolic acidosis (cord artery pH <7.05 and an extracellular fluid compartment base deficit >12.0 mmol/L), fetal scalp blood sampling, and operative deliveries. Comparisons of these outcomes were made between the initiation period (the first 2 years) and the subsequent usage period (the next 9 years).
RESULTS: In the whole study population the prevalence of cord pH <7.05 decreased from 1.5-0.81% (relative risk, 0.54; 95% confidence interval, 0.43-0.67), the rate of cesarean deliveries from 17.2-14.1% (relative risk, 0.82; 95% confidence interval, 0.89-0.97), and the rate of fetal scalp blood sampling from 1.75-0.82% (relative risk, 0.47; 95% confidence interval, 0.38-0.58) when the 2 study periods were compared. In the ST analysis group, the frequency of cord metabolic acidosis rate was reduced from 1.0-0.25% (relative risk, 0.33; 95% confidence interval, 0.15-0.72).
CONCLUSION: We provide evidence that the results improve over time and there is a learning curve in the introduction of the ST analysis method. This was demonstrated by the lower rates of metabolic acidosis and operative deliveries after the initial implementation period.